Prevalence of pseudobulbar affect symptoms and clinical correlates in nursing home residents. (2nd November 2015) - Foley, Kevin; Konetzka, R. Tamara; Bunin, Anthony; Yonan, Charles
Abstract : Objective: Pseudobulbar affect (PBA) is a neurological disorder of emotional expression, characterized by uncontrollable episodes of crying or laughing in patients with certain neurological disorders affecting the brain. The purposes of this study were to estimate the prevalence of PBA in US nursing home residents and examine the relationship between PBA symptoms and other clinical correlates, including the use of psychopharmacological medications. Methods: A retrospective study was conducted between 2013 and 2014 with a convenience sample of residents from nine Michigan nursing homes. Chronic‐care residents were included in the "predisposed population" if they had a neurological disorder affecting the brain and no evidence of psychosis, delirium, or disruptive behavior (per chart review). Residents were screened for PBA symptoms by a geropsychologist using the Center for Neurologic Study‐Lability Scale (CNS‐LS). Additional clinical information was collected using a diagnostic evaluation checklist and the most recent Minimum Data Set 3.0 assessment. Results: Of 811 residents screened, complete data were available for 804, and 412 (51%) met the criteria for the "predisposed population." PBA symptom prevalence, based on having a CNS‐LS score ≥13, was 17.5% in the predisposed population and 9.0% among all nursing home residents. Those with PBA symptoms were more likely to have a documented mood disorder and be using a psychopharmacological medication, including antipsychotics, than those without PBA symptoms. Conclusions: Pseudobulbar affect symptoms were present in 17.5% of nursing home residents with neurological conditions, and 9.0% of residents overall. Increasing awareness and improving diagnostic accuracy of PBA may help optimize treatment. © 2015 The Authors. International Journal of Geriatric Psychiatry Published by John Wiley & Sons Ltd.